PENGARUH BELANJA LANGSUNG DAN BELANJA TIDAK LANGSUNG TERHADAP PERENCANAAN ANGGARAN PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN (DISPERIN) KABUPATEN BANDUNG - Aditya Achmad Fathony; Siti Nurhayani (Fakultas Ekonomi UNIBBA, 2020)
This research aims to determine The Effect of Direct Expenditures and Indirect Expenditures to Budget Planning partially or simultaneously on the Office of Industry and Trade (DISPERIN) at Bandung Regency. The research method used descriptive and verification research methods with a quantitative approach. The results of study indicate that partially Direct Expenditures have a significant effect to Budget Planning for the next year, where these results are evidenced by the results of the t test Direct Expenditures obtain tcount greater than ttable, is -3.604> 2.776 with a significance value of 0.023 less than 0.05 (0.023 <0.05). Then the Indirect Expenditures partially do not have a significant effect on the next year's Budget Planning. This is evidenced by the ttest for Indirect Shopping to obtain tcount smaller than ttable, is 2.238 <2.776 with a significance value of 0.089 greater than 0.05 (0.089 <0.05). Simultaneously, Direct Expenditures and Indirect Expenditures have a significant effect to Budget Planning for the next year, this evidenced by the F test, the results of Fcount is greater than Ftable, is 7.639> 6.94 with a significance value of 0.043 less than 0.05 (0.043 <0.05). It can be concluded that simultaneously Direct Expenditures and Indirect Expenditures have a significant effect to Budget Planning at the Office of Industry and Trade (DISPERIN) Bandung Regency